Pengaruh Model Inkuiri Terbimbing terhadap Keterampilan Proses Sains Peserta Didik Kelas VIII SMP Negeri 55 Makassar - Fardha Tillah; Nurhayani H. Muhiddin; Hasanuddin Hasanuddin (Celebes Science Education, 2026)
This research aims to determine: 1) The level of science process skills of students at SMP Negeri 55 Makassar who are taught using the guided inquiry learning model. 2) The level of science process skills of students at SMP Negeri 55 Makassar who are taught using the direct learning model. 3) Improving the science process skills of class VIII students at SMP Negeri 55 Makassar who are taught using the guided inquiry learning model. This type of research is Quasi Experimental Design research and Group Pretest-Posttest Design research design. The population of this study was all students in class VIII of SMP Negeri 55 Makassar which consisted of 2 classes with a total of 42 students. The sample was selected using the Saturated Sampling technique and obtained 21 students from class VIII.A as the experimental class and VIII.B 21 students as the control class. The research instrument is a 16-item multiple choice test of science process skills. Data were analyzed using descriptive and inferential statistics. The results of the research show that: The level of Science Process Skills of class VIII students at SMP Negeri 55 Makassar who were taught using the guided inquiry learning model was in the medium category with a score of 12.14. The level of Science Process Skills of class VIII students at SMP Negeri 55 Makassar who are taught using the direct learning model is in the low category with a score of 8.38. Improving the Science Process Skills of class VIII students at SMP Negeri 55 Makassar using the guided inquiry learning model is in the medium category with an N-Gain of 0.56. Improving the Science Process Skills of class VIII students at SMP Negeri 55 Makassar using the direct learning model is in the medium category with an N-Gain of 0.35.